Macronutrient and Micronutrient Content in Breast Milk - Subandrate Subandrate; Ella Amalia; Medina Athiah; Safyudin Safyudin; M. Nadhif Prasetyo; M. Hafizh Arrafi (Conferences of Medical Sciences Dies Natalis, 2021)
Breast milk is the best source of nutrition for newborns. Breast milk content is composed of water, protein, carbohydrates, fats, vitamins, minerals, antibodies, and enzymes. Breast milk also contains white blood cells and substances that make up the baby`s immune system such as immunoglobulins and lysozyme. The composition of breast milk can change depending on the needs and ages of the baby. Exclusive breastfeeding is recommended by many doctors and other healthcare professionals. One of the factors that influence exclusive breastfeeding is the mother`s knowledge about the content of breast milk. Most breastfeeding mothers do not know the nutritional content of breast milk, both macronutrients, and micronutrients. Breast milk is also rich in immune cells, antibodies, and other bioactive ingredients that help protect the baby from infection until the baby has an effective antibody response in the first few months of life. Breast milk is an ideal nutrient for babies. The mixture of vitamins, proteins, and fats in breast milk can provide the nutrients and calories the baby needs to grow. Babies who have been breastfed for 6 months are more likely to reach their ideal weight.Therefore, the government recommends exclusive breastfeeding for infants up to the age of 6 months.